The effects of glyphosate and aminopyralid on a multi-species plant field trial - Pfleeger, Thomas (Ecotoxicology (London, England), 2012)
In the United States, the US EPA has the responsibility for the registration of pesticides. For the protection of nontarget terrestrial plants this requires two simple greenhouse tests (seedling emergence and vegetative vigor), each done with ten species grown individually. Indications of unacceptable effects levels equivalent to environmental exposure can lead to field testing which is not well-defined. Our objective was to develop a regional field test that is simple, economical, geographically flexible and with endpoints of ecological significance and compare the results with the standard greenhouse tests. Three native Oregon plant species were grown together with an introduced species. The experiment was replicated at two locations and repeated for 3 years with glyphosate applied at 0, 0.01 (8.3 g/ha), 0.1 (83.2 g/ha), and 0.2 (166.4 g/ha) × FAR (Field Application Rate of 832 gm/ha acid equivalent) and 2 years with aminopyralid applied at 0, 0.037 (4.6 g/ha), 0.136 (16.7 g/ha), and 0.5 (61.5 g/ha) × FAR (123 g/ha acid equivalent). With glyphosate, plant height and volume decreased with increasing herbicide concentration for all species, and for nearly all farm × year combinations. With aminopyralid, one species died at nearly all concentrations, sites and years, while the effects on the other three species were less pronounced and variable. The relative rank in glyphosate sensitivity among species in the field studies differed from the ranking from greenhouse studies, with Cynososurs echinatus the most sensitive in the field but Prunella vulgaris the most sensitive in the greenhouse. With aminopyralid, sensitivity generally was similar for all species in the greenhouse as in the field. The results suggest that a simple field test can be successfully designed to investigate the ecological effects of herbicides on plant communities and supplement information gained from greenhouse tests performed in controlled environments